Comparative Performance of PLZT and PVDF Pyroelectric Sensors Used to the Thermal Characterization of Liquid Samples - Gemima Lara Hernandez; Alfredo Cruz-Orea; Ernesto Suaste Gomez; Jose Jesus Agustin Flores Cuautle (Advances in Materials Science and Engineering)
Among the photothermal methods, the photopyroelectric (PPE) technique is a suitable method to determine thermal properties of different kinds of samples ranging from solids to liquids and gases. Polyvinylidene difluoride (PVDF) is one of the most frequently used pyroelectric sensors in PPE technique but has the disadvantage that it can be easily deformed by the sample weight. This deformation could add a piezoelectric effect to the thermal parameters assessment; also PVDF has a narrow temperature operation range when compared with ceramic pyroelectric sensors. In order to minimize possible piezoelectric effects due to sensor deformation, a ceramic of lanthanum modified lead zirconate (PLZT) was used as pyroelectric sensor in the PPE technique. Then, thermal diffusivity of some liquid samples was measured, by using the PPE configuration that denominated the thermal wave resonator cavity (TWRC), with a PLZT ceramic as pyroelectric detector. The performance obtained with the proposed ceramic in the TWRC configuration was compared with that obtained with PVDF by using the same configuration.